(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Balabust N. Yu., Blazhevych Yu. I. Teachers’ Training Process in Podillya Region On the Basis of Church School and Two-Years Educational Institutions (end of XIX – beginning of XX century). This paper investigates a place and a role of church schools in the training of teachers in Podillya region in the late XIX – early XX century and is based on documentary and archival materials, publications, periodicals. The author also analyzes the cooperation between network of church schools and teachers training institutions which are directly related: two-years educational institutions and church teachers’ schools. The article highlights the substance, the essence and the concept of this process, it the estimates a purpose, objectives, forms and methods of educational work in the spiritual and educational institutions, their organizational structure, logistics, students andfaculty specifics etc.